Evaluation of Processes for Mechanical Manufacturing of Composite Materials for Li‐Sulfur Batteries. Issue 4 (15th February 2018) - Titscher, Paul; Zellmer, Sabrina; Burmeister, Christine F.; Schmidt, Lars O.; Breitung‐Faes, Sandra; Garnweitner, Georg; Kwade, Arno
Abstract: Lithium‐sulfur batteries are a promising alternative to lithium‐ion batteries due to their low weight and the high availability of sulfur. In addition to research on material aspects, scalable processes are needed to manufacture tailored sulfur cathodes with high‐energy densities. Therefore, this work focuses on the usage of mechanical processes to prepare defined carbon‐sulfur composite materials that are subsequently processed to electrodes. DEM simulations are used to calculate the necessary power input and the resulting stress energy for different mechanical processes. Abstract : The manufacturing of carbon‐sulfur composite material via ball mill processes is investigated. The performance of the composite materials for energy storage applications is analyzed and correlated with the process parameters. The particle size is identified as the major characteristic to influence the energy density and lifetime of the battery.